2016
DOI: 10.1177/1363460715583606
|View full text |Cite
|
Sign up to set email alerts
|

Live like a king, y’all: Gender negotiation and the performance of masculinity among Southern drag kings

Abstract: This paper draws upon interviews with 27 drag kings in the South to examine why individuals perform drag, the range of performance experiences, and how drag kinging challenges dichotomous ideas about gender. We use these interviews to demonstrate the importance of context in understanding the drag king culture. We clearly show that in the South the performance of masculinity in the form of drag differs from other areas of the country. Our findings indicate that Southern drag kings, in general, do not overtly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…Work by historian Brock Thompson () on queer Arkansas suggests that Southern cultural norms of pageantry support public visibility of cross‐dressing and drag. Sociological work on drag in the South is limited, apart from Rupp and Taylor () ethnography of a drag queen cabaret in Key West, Florida, and Baker Rogers' work on drag kings in the South (Baker & Kelly, ). Both studies illustrate the importance of context in understanding the role of drag in individuals' lives.…”
Section: The Stakes Of Expanding Our Researchmentioning
confidence: 99%
“…Work by historian Brock Thompson () on queer Arkansas suggests that Southern cultural norms of pageantry support public visibility of cross‐dressing and drag. Sociological work on drag in the South is limited, apart from Rupp and Taylor () ethnography of a drag queen cabaret in Key West, Florida, and Baker Rogers' work on drag kings in the South (Baker & Kelly, ). Both studies illustrate the importance of context in understanding the role of drag in individuals' lives.…”
Section: The Stakes Of Expanding Our Researchmentioning
confidence: 99%
“…Although respondents’ gender and sexual identities vary, all respondents in this study have identified as a drag king at some point in their lives. Drag kings are “any person who performs masculinity within the context of a drag show or contest” (Baker and Kelly 2016, 48). This broad definition captures a community, history, and culture that Halberstam (1997, 106) explained is “necessarily multiple.” Drag kinging in the United States began largely within lesbian subcultures in the 1990s and provided an outlet for women to perform masculinities (Halberstam 1997, 1998).…”
Section: Drag Kinging and Gender Identitymentioning
confidence: 99%
“…This broad definition captures a community, history, and culture that Halberstam (1997, 106) explained is “necessarily multiple.” Drag kinging in the United States began largely within lesbian subcultures in the 1990s and provided an outlet for women to perform masculinities (Halberstam 1997, 1998). While historically masculinities were viewed as nonperformative—as the norm to measure other gender performances against (Butler 1990)—today drag kinging has become more widespread and provides an outlet for people of various gender identities and sexualities to explore masculinity in a safe and entertainment-focused context (Baker and Kelly 2016; Piontek 2002; Rupp, Taylor, and Shapiro 2010; Shapiro 2007).…”
Section: Drag Kinging and Gender Identitymentioning
confidence: 99%
“…These dual approaches have become entrenched in the theoretical and empirical accounts that followed and coalesce as a recognizable field of study. As a result, subsequent work on drag kinging can be divided into the analytic categories of performer and audience: as either a performative practice of gendered or sexual identity (Barbé i Serra, 2014; Grey, 2011; Halberstam, 1997, 1998; Hanson, 2007; LeBesco et al., 2002; Shapiro, 2007), or as a destabilizing political strategy derived from queer cultural membership (Baker and Kelly, 2016; Braziel, 2005; Escudero-Alías, 2011; Halberstam, 2001, 2003, 2005; Hobson, 2013; LeBesco et al., 2002; Pauliny, 2013).…”
Section: Scene Perspectivesmentioning
confidence: 99%